Consanguinité, Isonymie et Age Précoce au Mariage dans les deux Provinces de Tétouan et M’diq-fnideq (Maroc) - Hajjaji, Mohamed; Khadmaoui, Abd Errazzak; Soulaymani, Abd El-Majid; Azzouzi, Younes (European Scientific Journal, ESJ, 2018)
The purpose of this work is to contribute to the description of marital practices in Northern Morocco, to follow the evolution of these practices, and to determine the motives for marriages between relatives. Thus our results show a highly significant positive correlation between the age of the two spouses (r = 0.619, p <0.001), with the mean age of the mothers being 49.03 ± 6.56 years, while for the fathers it is 56,02 ± 6,16 years with a difference of 7 years between the two spouses in the current generation. For consanguineous marriages, we identified 51 relatives, namely a frequency of 25.4% for the generation of studied couples GCE, 13.3% for the generation of paternal grandparents GGPP, and 17.5% for the generation of maternal grandparents GGPM. The intergenerational comparison reveals a highly significant increase in the percentage of consanguinity, ranging from the generation of grandparents (15.4%) to that of the studied couples (25.4%), with a difference of 10% (p˂0.001). These results also show that there is a strong association between the prevalence of consanguineous marriages and the group of women under 19 years old (p = 0.002), whereas for husbands it is noted that There is no association between marital status and age at marriage. The coefficient of consanguinity estimated by isonymy is almost twice as large as the coefficient of inbreeding estimated by genealogy.